Pelatihan Pemanfaatan Peta Timbul sebagai Media Pembelajaran Bagi Guru Ilmu Pengetahuan Sosial (IPS) - Lasaiba, Mohammad Amin (Universitas Pattimura, 2023)
The training on creating raised-relief maps for Social Studies (IPS) teachers in Ambon City is an important initiative to enhance students' understanding of regional topography. With a holistic approach that involves a series of structured stages, the training aims to provide teachers with strong knowledge and skills in creating and using raised-relief maps as effective learning tools. The methodology includes identifying the initial needs of the teachers, selecting experienced instructors, preparing relevant training materials, and conducting the training through a series of structured sessions. Following the training, follow-up activities are carried out through monitoring, mentoring, and evaluating long-term impacts. The results of the training are expected to improve teachers' ability to create informative raised-relief maps and effectively utilize them in the learning process. Raised-relief maps are expected to better visualize the topographical characteristics of the region to students, enriching their learning experience. Thus, the training is anticipated to significantly enhance the quality of teaching and help students better understand the environment they live in.